Surveillance in the service of safety - Rashid Jooma (2279884) (2015)
The World Report on Road Traffic Injury Prevention of 2004 recommended that the newly motorizing countries establish road injury surveillance to define the burden, identify high-risk groups, plan intervention and monitor their impact. Despite its stated importance in the literature, very few examples of sustained surveillance systems are reported from low income countries. This presentation shares the results of an urban RTI surveillance program that has been running for the past 8 years since 2007 in the emergency departments of five major hospitals in Karachi, Pakistan. We describe the process of establishing the road injury surveillance system incorporating a multi-institution research group including physicians and transportation engineers. Data was collected from 5 city-wide hospitals with details of the injury, severity scoring and information of the circumstances of the crash. Site visits supplemented this data and the results were disseminated to municipal authorities along with low cost engineering solutions to rectify hazards in the road network. In the 8 years between 2007 and 2014, 262,269 road injury victims were registered by the surveillance system. Though 76% of the injuries were categorized as “minor”, 20% led to hospital admission and in 3% deaths occurred. The information on location of crashes and site visits led to an extensive catalogue of road network hazards and their rectification led to demonstrated reductions in crash frequency. Data was also used for safety advocacy in groups found to be vulnerable in the surveillance, such as motorcyclists, road sweepers and school going pedestrians. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.65